Identification of keratinocyte growth factor as a target of microRNA-155 in lung fibroblasts: implication in epithelial-mesenchymal interactions. - Nicolas Pottier (Public Library of Science (PLoS), 2009)
Background Epithelial-mesenchymal interactions are critical in regulating many aspects of vertebrate embryo development, and for the maintenance of homeostatic equilibrium in adult tissues. The interactions between epithelium and mesenchyme are believed to be mediated by paracrine signals such as cytokines and extracellular matrix components secreted from fibroblasts that affect adjacent epithelia. In this study, we sought to identify the repertoire of microRNAs (miRNAs) in normal lung human fibroblasts and their potential regulation by the cytokines TNF-alpha, IL-1beta and TGF-beta. Methodology/principal findings MiR-155 was significantly induced by inflammatory cytokines TNF-alpha and IL-1beta while it was down-regulated by TGF-beta. Ectopic expression of miR-155 in human fibroblasts induced modulation of a large set of genes related to "cell to cell signalling", "cell morphology" and "cellular movement". This was consistent with an induction of caspase-3 activity and with an increase in cell migration in fibroblasts tranfected with miR-155. Using different miRNA bioinformatic target prediction tools, we found a specific enrichment for miR-155 predicted targets among the population of down-regulated transcripts. Among fibroblast-selective targets, one interesting hit was keratinocyte growth factor (KGF, FGF-7), a member of the fibroblast growth factor (FGF) family, which owns two potential binding sites for miR-155 in its 3'-UTR. Luciferase assays experimentally validated that miR-155 can efficiently target KGF 3'-UTR. Site-directed mutagenesis revealed that only one out of the 2 potential sites was truly functional. Functional in vitro assays experimentally validated that miR-155 can efficiently target KGF 3'-UTR. Furthermore, in vivo experiments using a mouse model of lung fibrosis showed that miR-155 expression level was correlated with the degree of lung fibrosis. Conclusions/significance Our results strongly suggest a physiological function of miR-155 in lung fibroblasts. Altogether, this study implicates this miRNA in the regulation by mesenchymal cells of surrounding lung epithelium, making it a potential key player during tissue injury.